2016
DOI: 10.1073/pnas.1522987113
|View full text |Cite
|
Sign up to set email alerts
|

Human DDX3 protein is a valuable target to develop broad spectrum antiviral agents

Abstract: Targeting a host factor essential for the replication of different viruses but not for the cells offers a higher genetic barrier to the development of resistance, may simplify therapy regimens for coinfections, and facilitates management of emerging viral diseases. DEADbox polypeptide 3 (DDX3) is a human host factor required for the replication of several DNA and RNA viruses, including some of the most challenging human pathogens currently circulating, such as HIV-1, Hepatitis C virus, Dengue virus, and West N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 43 publications
1
110
0
Order By: Relevance
“…Under the condition of DNA damage and inflammation, aberration functions of DNA repair could promote the development of dysplastic lesion and subsequent HCC. Given that the small-molecule-mediated inhibition of DDX3X activity may provide new therapeutic opportunities to treat various viral infections and cancers (47,48), the impact of DDX3X on DNA damage and repair pathways cannot be underscored. A detailed understanding of the biology, pathology, and the complexity of the cellular responses to DNA damage in HCC associated with DDR deficiency will allow further preclinical investigations and provide appropriate treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Under the condition of DNA damage and inflammation, aberration functions of DNA repair could promote the development of dysplastic lesion and subsequent HCC. Given that the small-molecule-mediated inhibition of DDX3X activity may provide new therapeutic opportunities to treat various viral infections and cancers (47,48), the impact of DDX3X on DNA damage and repair pathways cannot be underscored. A detailed understanding of the biology, pathology, and the complexity of the cellular responses to DNA damage in HCC associated with DDR deficiency will allow further preclinical investigations and provide appropriate treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Other host targets. Several groups of compounds reported to target pleiotropic host targets, including ribosomes (lactimidomycin and its derivatives), the proteasome (bortezomib and its derivatives), DDX3 or HSP70, have demonstrated broad-spectrum antiflaviviral activity in vitro 12,15,118,231,232 . However, most of these compounds have side effects that severely limit their potential use as (prophylactic) antiviral agents.…”
Section: Polyamine Synthesis Inhibitorsmentioning
confidence: 99%
“…These findings indicate that aberrations in this gene result in loss of RNA-unwinding function and suppression of cell proliferation, thus contributing to the pathogenesis and poor prognosis of NKTCL. It has been reported that DDX3X is an important target for the development of broad-spectrum antiviral agents [38]. In lung cancer, a small molecule inhibitor (RK-33) targeting DDX3X was found to be effective in inducing apoptosis and promoting sensitization to radiation in DDX3X-overexpressing cell lines [39].…”
Section: Ddx3xmentioning
confidence: 99%